Using Technology to Increase Opportunities to Respond. (April 2019) - Rila, Ashley; Estrapala, Sara; Bruhn, Allison Leigh
Delivering high rates of opportunities to respond (OTR) has been shown to improve student outcomes for students with challenging behavior. High rates of OTR can maximize student engagement while providing ways for teachers to quickly assess student content mastery. Given the increasing trend of technology use in schools, teachers can leverage technology for delivering OTR. We discuss three technology-based tools teachers can use to enhance OTR delivery with examples of how to incorporate these tools into classrooms.